Validação de um álbum seriado para a prevenção do diabetes mellitus tipo II em adultos - Gama, Dedabrio Marques (2022)
Objective: to validate a flipchart aimed at the prevention and control of type II diabetes mellitus in adults. Method: This is a methodological, quantitative study carried out with nine expert judges in the health area and nine nurses from Primary Health Care in the city of Santa Maria, Rio Grande do Sul. Data collection was carried out between July and October 2021, using an instrument with a Likert-type scale to evaluate the serial album. Data were analyzed using descriptive statistics techniques. The study respects the ethical precepts in accordance with Resolutions 466/2012 and 580/2018. Results: The flipchart presented a global CVI of 0.90 by the expert judges and a totally adequate level of agreement between the expert judges in the health area and nurses. However, suggestions for improvements to the serial album were proposed, which were accepted and modified for the final version of the material. Final considerations: The flipchart was validated in terms of appearance and content, and can be considered in the context of educational activities as an instrument capable of favoring the prevention of type II diabetes mellitus in adults.